ADHD and Social Skills: A Step-by-Step Guide for Teachers and Parents - Rapoport, Esta M. (Rowman & Littlefield Publishers, 2009)
Children with attention-deficit/hyperactivity disorder (ADHD) leave for school in the morning with a smile and a backpack, ready to make friends. They often return from school after having been bullied. Children with ADHD appear vulnerable to their peers, because they misinterpret social cues and behave in a socially inappropriate manner. These children have few if any friends. This book explains the difficulties that children with ADHD endure to those individuals who do not understand the complexities of these children's problems. Difficulties with attention, organization and social interaction are listed, defined, and described. Teachers and personnel who work with these children in school and parents who work with their children at home are offered innovative techniques for improving these children's behavior, in a way that everyone can understand and implement. Real-life experiences of average people living with children with ADHD are included, so that parents can feel less alone in their experiences.